Laser Ablation Synthesis in Solution of Nanoantimicrobials for Food Packaging Applications. Issue 1804 (2015) - Sportelli, Maria C.; Ancona, Antonio; Picca, Rosaria A.; Trapani, Adriana; Volpe, Annalisa; Trapani, Giuseppe; Cioffi, Nicola
ABSTRACT: Designing bioactive materials, with controlled metal ion release, exerting significant bioactivity and associated low toxicity for humans, is nowadays one of the most important challenges for the scientific community. In this work, we propose a new material combining the well-known antimicrobial properties of copper nanoparticles (CuNPs) with those of bioactive chitosan (CS), a cheap natural polymer widely exploited for its biodegradability and nontoxicity. Here, we used ultrafast femtosecond laser pulses to finely fragment, via laser ablation, a Cu solid target immersed into aqueous CS solutions. Homogeneously dispersed copper-chitosan (Cu-CS) colloids were obtained by tuning the Cu/CS molar ratios, according to the initial chitosan concentration, as well as other experimental parameters. Cu-CS colloids were characterized by several techniques, like UV-Vis and X-ray Photoelectron spectroscopies (XPS). Transmission Electron Microscopy (TEM) was used to morphologically characterize the novel nanocomposites.